Selection of key urban defense areas based on regional comprehensive risk assessment - WEI Hua, WANG Xiaoxia, YANG Fengbao, JIA Qi (Zhihui kongzhi yu fangzhen)
Aiming at the problem of how to select high risk key defense area under the condition of limited urban defense force, to maximize the utility of limited force and minimize the urban risk, this paper proposes a method of selecting key defense area based on regional comprehensive risk assessment. Firstly, a reasonable risk assessment index system is constructed from the perspective of the intruder and the defender. Secondly, based on the idea of equivalent energy, the weight product normalization method is proposed to determine the combined weight of the target risk index, and then calculate the target risk value. Then, according to the centroid theory, the weighted centroid calculation model of target distribution is constructed, and the dispersion matrix is established to calculate the dispersion of regional target distribution. Finally, the regional comprehensive risk assessment function is constructed according to the area of risk radar map, and the comprehensive risk of each region is quantitatively assessed according to the target situation of districts I to VI of a city. The results show that compared with the target risk coupling method, the proposed method can realize the regional comprehensive risk assessment more accurately, and provide decision-making basis for the selection of key urban defense areas and the efficient deployment of limited forces.